The Aurora B specificity switch is required to protect from non-disjunction at the metaphase/anaphase transition - Kelly, Joanna R. (Nat Commun, 2020)
The Aurora B abscission checkpoint delays cytokinesis until resolution of DNA trapped in the cleavage furrow. This process involves PKCε phosphorylation of Aurora B S227. Assessing if this PKCε-Aurora B module provides a more widely exploited genome-protective control for the cell cycle, we show Aurora B phosphorylation at S227 by PKCε also occurs during mitosis. Expression of Aurora B S227A phenocopies inhibition of PKCε in by-passing the delay and resolution at anaphase entry that is associated with non-disjunction and catenation of sister chromatids. Implementation of this anaphase delay is reflected in PKCε activation following cell cycle dependent cleavage by caspase 7; knock-down of caspase 7 phenocopies PKCε loss, in a manner rescued by ectopically expressing/generating a free PKCε catalytic domain. Molecular dynamics indicates that Aurora B S227 phosphorylation induces conformational changes and this manifests in a profound switch in specificity towards S29 TopoIIα phosphorylation, a response necessary for catenation resolution during mitosis.